Improving Understanding of Intellectual Property Legal Protection - Irawaty Irawaty; Sunyoto Sunyoto; Wara Dyah Pita Rengga; Aldias Bahatmaka; Godham Eko Saputro (Jurnal Panjar: Pengabdian Bidang Pembelajaran, 2025)
After Indonesia became a signatory to the General Agreement on Tariffs and Trade (GATT) in 1994, Indonesia already had regulations that became the legal basis for the protection of patents, copyrights, trademarks, trade secrets, integrated circuit layout designs, industrial designs, plant variety protection, and geographical indications. In Indonesia, of all the types of IP that have been written, only a few types of IP are quite popular, namely patents, copyrights, and trademarks. Based on the theory of legal awareness stated by Soerjono Soekamto, if someone knows a regulation then it is included in the category of having knowledge only. In fact, for each regulation, the community does not only stop at the level of knowledge but also the level of understanding, attitudes, and behavior to be able to know their legal awareness. In relation to IP regulations, the community (in relation to this community service activity, those who have the potential to own IP, namely Teachers and Students) is expected not only to stop at the level of knowledge but also at the level of behavior (in this case the expected behavior is, at least to record and/or register the IP they own). With the three pillars of IP stipulated, namely registration/recording, commercialization, and protection. IP regulations in Indonesia stipulate that IP that can be protected is IP that has been registered with the DJKI. In connection with the relative lack of understanding of high school/vocational school teachers and students in Semarang City related to the focus and three pillars of IP, it is urgent for the UNNES academic community to contribute significantly as a facilitator to improve the understanding of IP protection with a focus on Copyright for high school and vocational school teachers in Semarang City by conducting workshops and facilitating IP recording/registration.